Anorectal melanoma. - Jalleh, R.P.; Pathmanathan, R.; Krishnan, M.M.; Mukherjee, A. (1988)
Four cases of anorectal melanoma are presented. The authors believe that this is the first report of the occurrence of this tumour in Malays. Advanced disease at initial presentation accounts for the poor prognosis observed in this series. Surgery remains the principal treatment modality, although controversy exists regarding optimal extent of resection.